Spelling performance of public and private school students: A comparative study - Sampaio, Maria Nobre [UNESP] (2017)
To characterize and compare the spelling performance of private and public students. Three hundred 1st-5th graders from public and private schools in the city of Marília, São Paulo, Brazil, were evaluated, totalizing 30 students from each grade, respectively. Collective and individual versions of the Pró-Ortografia test (a renowned Brazilian spelling test) were administered. There were significant inter-group differences indicating that private school students achieved higher performance. The mean values of correct answers of higher grade level students were statistically greater than those of the lower grade level students. The results indicated that the mean values of correct answers of all versions of the spelling test administered increased across grades for both private and public school students. However, the data evaluated showed that private school students attained higher spelling performance than public school students from the 2nd grade onwards.